Implementation of Digital Marketing and Digital Payment in the Community of UMKM Cake Entrepreneurs : Penerapan Digital Marketing dan Digital Payment pada Komunitas UMKM Pengusaha Kue Etalase - Zarnelly, Zarnelly; Fronita, Mona; Afifah, Afifah Pendri (Institut Riset dan Publikasi Indonesia, 2025)
The current problem is the problem of promotion on social media and online sales, currently cake sales are done manually or conventionally so that it is not felt to be optimal, because it is often constrained by the weather, if it rains then cake sales are somewhat hampered, as well as during school holidays, because sales are still consignment or consignment systems, if they are not sold out then the cake producer bears the loss, in addition, in making transactions they have difficulty in providing change and storing coins, for that it is felt necessary to carry out mentoring activities for the implementation of digital marketing and digital payments to help overcome the problems of the UMKM community of cake showcase entrepreneurs. The community service method used is the PAR method, starting from problem identification, activity preparation, activity implementation and evaluation. The mentoring activity was attended by 11 participants consisting of cake producers and cake showcase entrepreneurs in Rumbai sub-district, the presentation material discussed the socialization of digital marketing and digital payment practices using the DANA application, at the end of the community service activity an evaluation was carried out with the results that 70% of participants were satisfied with the mentoring activities and wanted to implement digital marketing and digital payments in their businesses.